(untitled) (International journal of artificial intelligence, 2026)
This article explores modern diagnostic technologies used in therapeutic dentistry and their role in improving diagnostic accuracy and clinical decision-making. The focus is placed on contemporary methods applied in the diagnosis of caries, pulp and periapical diseases, and periodontal conditions. Digital radiography, optical diagnostic systems, electronic apex locators, pulp vitality tests, and digital periodontal diagnostics are analyzed as essential tools of modern therapeutic dental practice. The article emphasizes that advanced diagnostic technologies enable early detection of pathological changes, support minimally invasive treatment approaches, and improve long-term clinical outcomes. At the same time, it is highlighted that diagnostic technologies are most effective when combined with thorough clinical examination and professional interpretation.